2021
DOI: 10.1371/journal.pone.0256695
|View full text |Cite
|
Sign up to set email alerts
|

Match-related physical performance in professional soccer: Position or player specific?

Abstract: The purpose of this study was to examine to what extent the physical match performance of professional soccer players is both position and player specific. First, official match data from the 2019/20 German Bundesliga season was used to search for players that met the inclusion criteria of playing a minimum of four entire matches in at least two different playing positions. Overall, 25 players met the criteria prior to the COVID-19 induced break, playing a minimum of eight matches. Second, the physical match p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 31 publications
2
34
1
Order By: Relevance
“…Two studies already examined the extent to which the match performance of soccer players is not only position-specific, but also player-specific ( Schuth et al, 2016 ; Altmann et al, 2021 ). Altmann et al (2021) investigated the behavior of players that switched between playing positions (e.g., center back to full back).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies already examined the extent to which the match performance of soccer players is not only position-specific, but also player-specific ( Schuth et al, 2016 ; Altmann et al, 2021 ). Altmann et al (2021) investigated the behavior of players that switched between playing positions (e.g., center back to full back).…”
Section: Introductionmentioning
confidence: 99%
“…Two studies already examined the extent to which the match performance of soccer players is not only position-specific, but also player-specific ( Schuth et al, 2016 ; Altmann et al, 2021 ). Altmann et al (2021) investigated the behavior of players that switched between playing positions (e.g., center back to full back). Their results showed that 44–58% of the intraindividual changes in physical match performance due to the change in position can be explained by the factor playing position.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical match performance is one of the most studied topics in Sports Science since EPTS devices became a trend in soccer. Despite the vast number of publications, most research has focused on assessing player performance based on isolated metrics such as distance covered, accelerations, or high-intensity runs (HI) (Bradley et al 2013;Altmann et al 2021; Ingebrigtsen et al 2015). In addition, the tactical context tends to be widely simplified and often ignored.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many researchers have been doing research on the field to understand it further in terms of physiological and technical requirements (Rivilla-Garcia et al, 2019;Konefal et al, 2020). Recently, through match analysis, there has been an increase in the existing information on the distance players run (Brandley et al, 2018;Smpokos et al, 2018;Altmann et al, 2021). This is related to the fact that there have been developments in match analysis systems and that coaches are more keen on this subject (Rivilla-Garcia et al, 2019).…”
Section: Introductionmentioning
confidence: 99%